The preparation of thin-walled multi-cavities β-cyclodextrin polymer and its static and dynamic properties for dyes removal. (1st September 2019) - Chen, Jianxin; Liu, Mengling; Pu, Yunping; Wang, Chongbin; Han, Jian; Jiang, Minghuang; Liu, Kaili
Abstract: Thin-walled multi-cavities β-cyclodextrin polymers (Hβ-CDs) were prepared by the suspension polymerization method using SiO2 nanoparticles as a template. The components and morphology structure of Hβ-CDs were characterized by FTIR, BET, SEM, and TEM. The adsorption performances of the prepared nano-adsorbent Hβ-CDs on crystal violet (CV), heavy metal ions, some cationic, neutral, and anionic dyes were investigated. The influences of the pH and ionic strength on CV adsorption by the Hβ-CDs were explored. The correlation coefficient ( R 2 ) of pseudo-second-order kinetic model reached 0.9984 and the adsorption isotherm was closer to the Langmuir model. As the temperature increased, the R 2 of the Freundlich isotherm model rose. Compared to anionic ones and heavy metal ions, Hβ-CDs had a better adsorption efficiency for cationic dyes. Dynamic adsorption also indicated the thin-walled multi-cavities structure was beneficial for improving absorptivity and application of β-cyclodextrin polymers. In addition, the Hβ-CDs exhibited potentially applicable for the regeneration and reuse with the removal efficiency of CV was as high as 89% in the fourth cycle. Graphical abstract: Image 10123 Highlights: Thin-walled multi-cavities β-CD polymers were successfully structured and prepared. Static and dynamic adsorption indicted the effect of the thin-walled multi-cavities structure for β-CD polymers. High ionic strength was beneficial to dyes adsorption. Adsorption-degradation cycles were successfully designed.